Gula Darah Terkontrol Pada Pasien Diabetes Melitus Tipe 2 Dengan Dermatofitosis di BRSUD Tabanan - Ni Wayan Heanly Rusdrajiani Dewi; Ni Made Indah Puspasari; Asri Lestarini (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Diabetes Mellitus (DM) is a livable disease and its increased every year. (DM) victim are prone to skin infections, one of which is dermatophytes. Uncontrolled blood sugar levels in DM patients are prone to dermatophytosis. The objective of research was to understand correlation controlled blood sugar and dermatophytosis in patients with type2 diabetes mellitus. The research done in research an analytical observational use case control type. The minimum sample number of cases is 35 people and the minimum sample of control is 35 people acording with the requirement of inclusion and exclusion. The research is worked in the Tabanan General Hospital in 2020 – 2021 using medical records which was then analyzed univariately to see the characteristics of the subject and the comparison of the proportions of each group. Chi-square testing was used to know the correlation between blood sugar control and dermatophytosis. The p-value<0.05 was said to be statistically significant and the p-value>0.05 was said to be insignificant. In the dermatophytosis group, the majority (45.7%) of study subjects were old 31-60 years and majority (62.9%) male. The results of bivariate analysis showed that there was no significant difference in proportion of sex and age in the dermatophytotic and non-dermatophytic groups. The most common dermatophytosis was tinea cruris with a proportion of 37.1%. The bivariate analysis showed that there was no significant correlation between blood sugar control and dermatophytosis in type2 diabetes mellitus patients (value p = 0.454; OR = 1.45). The conclusion is that there is no significant correlation between blood sugar control and dermatophytosis in type2 diabetes mellitus victim at Tabanan General Hospital. Several factors that influence the research are differences in blood sugar classification standards, differences in basic characteristics, environmental conditions.